The potential role of integrin alpha 6 in human mesenchymal stem cells - Al-Obaide, Mohammed; Ishmakej, Albi; Brown, Christina; Mazzella, Matteo; Agosta, Patrina; Perez-Cruet, Mick; Chaudhry, G. Rasul (Frontiers in Genetics, 2022)
The long non-coding (lnc) antisense RNA transcripts regulate the fate of human mesenchymal stem cells (hMSCs) with potential therapeutic implications. The ITGA6 gene is one of the integrin alpha gene family members encoding integrin subunit alpha 6 considered critical in the hMSCs differentiation and may regulated by lncRNA. The bioinformatic analysis showed that ITGA6 genomic space hostsITGA6 antisense RNA (ITGA6-AS1) mapped on the reverse strand overlapping ITGA6 exon-2. We then investigated the potential correlation between the expression of ITGA6 and one of lncRNA, ITGA6 antisense RNA (ITGA6-AS1) in hMSCs derived from bone marrow (BM), and six perinatal tissues, chorion (CH), cord placenta junction (CPJ), cord tissue (CT), placenta (PC), and Wharton’s jelly (WJ). The results showed ITGA6 expression was inversely correlated with ITGA6-AS1 expression in MSCs from various sources. Expression of ITGA6 was higher, and ITGA6-AS1 was lower in MSCs from BM, CPJ, CT, and WJ (P<0.05). In contrast, IAGA6 expression was lower, and ITGA6-AS1 was higher in MSCs from CH and PC (P<0.05). We conclude that the post-transcriptional regulation of the ITGA6 in hMSCs is controlled by the ITGA6-AS1, which suggests it is one of the critical factors in the heterogeneity of human mesenchymal stem cells.